2019
DOI: 10.2478/linpo-2019-0001
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of research on reading in English on screen and on paper

Abstract: The introduction and wide use of devices, especially mobile ones, has changed the way learners read and do research for a variety of reasons, and this trend has attracted a number of studies conducted regarding reading on screen and on paper in addition to those dealing with the students’ behavior in using online resources to print ones. This paper aims at identifying the major findings and trends in reading research by describing the current state of knowledge and practice in the studies comparing reading on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Given the results of the present study, testing intervention strategies designed to make Intro Psych a more even playing field for E/ SEA international students also seems like a fruitful area for future work. For example, a growing body of research examines differences in the effectiveness of reading in print versus online, where digital language tools like dictionaries and translators may be available (see Çetin & Kiliçkaya, 2019).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Given the results of the present study, testing intervention strategies designed to make Intro Psych a more even playing field for E/ SEA international students also seems like a fruitful area for future work. For example, a growing body of research examines differences in the effectiveness of reading in print versus online, where digital language tools like dictionaries and translators may be available (see Çetin & Kiliçkaya, 2019).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Reading is the most crucial part of English teaching (Liu et al, 2020) that involves the interaction of readers with the text at specific times and contexts of culture, social, and physical environment to construct meanings (Çetin & Kılıçkaya, 2019). In recent years, the transformation of traditional reading material to electronic texts is gaining much attention because it promotes more complex, fluid, and multifaceted competencies that involve the integration of multimodal texts and digital screens (Xodabande & Hashemi, 2022).…”
Section: Offline Vs Online Readingmentioning
confidence: 99%
“…In contrast, L2 students seemed to divide their attention between macro-and micro-level supports when presented with information simultaneously. Additionally, Çetin and Kılıçkaya (2019) have reviewed articles published between 2009 and 2017 about reading on paper or screen. They state that the reviewed studies are inconclusive but provide enlightening findings.…”
Section: Offline Vs Online Readingmentioning
confidence: 99%
“…In addition, a systematic review conducted by Çetin and Kılıçkaya (2019) raised concerns that digital texts may negatively affect learners because of the increased cognitive demands. These negative effects were especially pronounced when the screen optimisation and font size were not optimal, and the individuals experienced increased visual fatigue.…”
Section: Environmental Disadvantagesmentioning
confidence: 99%
“…Preferences are an individual's expression of what they like or dislike. The research examined in this scoping review shows that the individuals/participants in the research reviewed showed mixed preferences for paper or printed text(Çetin & Kılıçkaya, 2019;Haddock et al, 2020;Hou et al, 2017b;Krishen et al, 2016;Ross et al, 2017;Sage et al, 2019) Çetin and Kılıçkaya, (2019), in a systematic review, concluded that in some studies the students preferred reading digital text but in other studies the students preferred reading paper. The studies highlighted the importance of recognising additional factors that influence an individual's preferences.…”
mentioning
confidence: 97%